Anti-Inflammatory Effects of Dimethyl Fumarate in Microglia via an Autophagy Dependent Pathway - Lee, Young-Sun; Gupta, Deepak Prasad; Park, Sung Hee; Yang, Hyun-Jeong; Song, Gyun Jee (Frontiers in Pharmacology, 2021)
Dimethyl fumarate (DMF), which has been approved by the Food and Drug Administration for the treatment of relapsing-remitting multiple sclerosis, is considered to exert anti-inflammatory and antioxidant effects. Microglia maintain homeostasis in the central nervous system and play a key role in neuroinflammation, while autophagy controls numerous fundamental biological processes, including pathogen removal, cytokine production, and clearance of toxic aggregates. However, the role of DMF in autophagy induction and the relationship of this effect with its anti-inflammatory functions in microglia are not well known. In the present study, we investigated whether DMF inhibited neuroinflammation and induced autophagy in microglia. First, we confirmed the anti-neuroinflammatory effect of DMF in mice with streptozotocin-induced diabetic neuropathy. Next, we used in vitro models including microglial cell lines and primary glial cells to examine the anti-inflammatory and neuroprotective effects of DMF. We found that DMF significantly inhibited nitric oxide and proinflammatory cytokine production in lipopolysaccharide-stimulated microglia and induced the switch of microglia to the M2 state. In addition, DMF treatment increased the expression levels of autophagy markers including microtubule-associated protein light chain 3 (LC3) and autophagy-related protein 7 (ATG7) and the formation of LC3 puncta in microglia. The anti-inflammatory effect of DMF in microglia was significantly reduced by pretreatment with autophagy inhibitors. These data suggest that DMF leads to the induction of autophagy in microglia and that its anti-inflammatory effects are partially mediated through an autophagy-dependent pathway.